COMMON FACETS OF THE WORK OF TWO POETS - B. Abdurahmonova; O. Abdurahmonova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article covers common views on the role of Khwarazmiy and Alisher Navoi, mature figures of Uzbek classical literature. Some interesting facts are presented in the context of their works.